2015
DOI: 10.46743/2160-3715/2015.2433
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Russian Online Gift-Exchange Communities: The Results of Nethnographic Approach

Abstract: This paper reports on a two-week nethnographic (online) observation of four online gift-exchange communities – virtual platforms, where participants conduct barter exchange of different daily objects such as books, children's products, furniture, home ware and others. These communities as case of informal economy initially do not have formal attributed rules. It is essential to find out (1) which rules and mechanisms exist in this type of economy; (2) what motivates people who are not acquainted with another t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Two studies (3%) tested how people in online communities use emoticons to express feelings (Hakala et al, 2017;Tiidenberg, 2016), and one study revealed that this non-verbal communication is an important part of online interactions (Dineva et al, 2017). Nine studies (11%) mentioned including multiple forms of data, such as textual and graphical files (Gebauer et al, 2013); video, photos, and chats ; photographs and screen captures (Torres, 2017); photo galleries from the community (Polukhina & Strelnikova, 2015); voice and video files (Halabi et al, 2017); and pictorial and video footage posted by members ; however, these studies do not give an explanation of or clearly state how to incorporate both text and visuals into an analysis.…”
Section: Geographies and Methodologiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Two studies (3%) tested how people in online communities use emoticons to express feelings (Hakala et al, 2017;Tiidenberg, 2016), and one study revealed that this non-verbal communication is an important part of online interactions (Dineva et al, 2017). Nine studies (11%) mentioned including multiple forms of data, such as textual and graphical files (Gebauer et al, 2013); video, photos, and chats ; photographs and screen captures (Torres, 2017); photo galleries from the community (Polukhina & Strelnikova, 2015); voice and video files (Halabi et al, 2017); and pictorial and video footage posted by members ; however, these studies do not give an explanation of or clearly state how to incorporate both text and visuals into an analysis.…”
Section: Geographies and Methodologiesmentioning
confidence: 99%
“…However, we are confident that our systematic and thorough assessment of the selected manuscripts provides a more nuanced, integrated and robust understanding of the field of conflict in online communities. "brand-mediated moral conflict" OR conflict OR "interpersonal conflict" OR "public conflict" OR "consumer conflict" OR "social conflict" OR "online conflicts" OR "conflict culture" OR "heterogeneity in consumer collectives" OR "consumer aggression" OR "consumer revenge" OR "brand tribalism" OR "oppositional brand loyalty" OR "conflict culture" OR trolling OR e-dispute OR "online community conflict" OR "consumer schadenfreude" Keyword theme No.2 (Managing conflict) "conflict resolution" OR "conflict resolution strategies" OR "moderation practices" OR "conflict management" OR "conflict management strategies" OR "online dispute resolution" OR ODR OR "corporate governance" OR "community governance" Keyword theme No.3 (Context) "online brand community" OR "virtual community" OR "online community" OR "consumer communities" OR "social networking sites" OR SNSs OR "brand fan pages" OR "brand fans" OR "consumption communities" OR "communal consumption" OR "consumer collective" -Russia (Polukhina & Strelnikova, 2015) -USA (Boon, Pitt, & Salehi-Sangari, 2015) -Cross-countries (USA, Singapore, India, Sweden) N/A (literature review; conceptualization; or Not explicated stated)…”
Section: Conclusion and Limitationsmentioning
confidence: 99%
See 3 more Smart Citations